2008
DOI: 10.1086/520872
|View full text |Cite
|
Sign up to set email alerts
|

The Supernova Channel of Super‐AGB Stars

Abstract: We study the late evolution of solar metallicity stars in the transition region between white dwarf formation and core collapse. This includes the superYasymptotic giant branch (super-AGB, SAGB) stars, which ignite carbon burning and form an oxygen-neon (ONe) core. SAGB star cores may grow to the Chandrasekhar mass because of continued H-and He-shell burning, ending as core-collapse supernovae. From stellar evolution models we find that the initial mass range for SAGB evolution is 7:5Y9:25 M . We perform calcu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
426
1
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(462 citation statements)
references
References 61 publications
29
426
1
6
Order By: Relevance
“…A recent comparison between the inferred properties of massive O and B stars within 500 pc (Hohle et al 2010) using three modern evolution codes (Schaller et al 1992;Bertelli et al 1994;Claret 2004) indicate uncertainties at the ∼20 -25 % level. Similar degrees of uncertainty were found when computing the mass limits associated with O-Ne-Mg core formation in intermediate mass stars (Poelarends et al 2008).…”
Section: The Current Framework For Computing Evolutionsupporting
confidence: 68%
“…A recent comparison between the inferred properties of massive O and B stars within 500 pc (Hohle et al 2010) using three modern evolution codes (Schaller et al 1992;Bertelli et al 1994;Claret 2004) indicate uncertainties at the ∼20 -25 % level. Similar degrees of uncertainty were found when computing the mass limits associated with O-Ne-Mg core formation in intermediate mass stars (Poelarends et al 2008).…”
Section: The Current Framework For Computing Evolutionsupporting
confidence: 68%
“…In the following I summarize the main results of self-consistent fully evolutionary studies of these stars. However, for the sake of conciseness only a brief overview of the very interesting physical phenomena occurring during the carbon burning phase in this mass interval will be given, and I refer 54 E. García-Berro the interested reader to the series of papers by Ritossa et al (1996), García-Berro et al (1997), Iben et al (1997), Ritossa et al (1999), the more recent studies of Siess (2006Siess ( , 2007Siess ( , 2009Siess ( , 2010 which confirm the main findings of the previous papers, and Poelarends et al (2008). Also, the possible outcomes of the evolution of SAGB stars will be analyzed, but I will not discuss here other interesting aspects, like the possible contribution of this range of masses to r-process nucleosynthesis (Ning et al 2007, Wanajo et al 2006.…”
Section: The Formation and Evolution Of One White Dwarfssupporting
confidence: 56%
“…This is because the mass-loss rate depends on the metallicity of the envelope, which depends on the prescription adopted for determining the position of the inner edge of the convective envelope (Gil-Pons et al 2005, 2007. However, in contrast to what occurs for normal AGB stars, the number of thermal pulses necessary to remove the massive envelope is in this case very large, ∼10 3 (Poelarends et al 2008). Following the evolution during the thermally pulsing phase is thus a hard task, and we rely on approximations.…”
Section: Possible Outcomes Of Sagb Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that the initial mass range for producing EC SNe is smaller in single stars (Poelarends et al 2008) compared to binary stars in non-degenerate systems (Podsiadlowski et al 2004). …”
Section: The Zams Progenitor Masses Of Our Naked Helium Starsmentioning
confidence: 99%